Optimizing Emergency Department Length of Stay via Patient Flow Policy - Heryana, Ade; Suhartika, Eka; Handayani, Putri; Azteria, Veza (Lembaga Penerbitan Universitas Esa Unggul, 2025)
AbstractEmergency Department Length of Stay (EDLOS) is a key indicator of hospital service quality. Extended EDLOS contributes to overcrowding, increased risk of adverse events, treatment delays, prolonged hospitalization, and higher mortality rates. This study aimed to evaluate arrival and departure policies to control EDLOS in a class B regional government hospital in West Jakarta. A quantitative approach was used to analyze 30,710 emergency visit records and 18,036 triage visit records from January to December 2022. Total sampling was applied, with bivariate binary logistic regression used to analyze arrival policy and a generalized linear model for departure policy. The results showed a median EDLOS of 4 hours and 32 minutes, with 22.7% of cases exceeding the 8-hour service standard. Arrival policies for morning shifts differ from those for day and night shifts, while departure policies remain consistent across all shifts. To prevent EDLOS exceeding 8 hours in the morning shift, priority should be given to children–adolescents, adults, and elderly patients over toddlers, psychiatric over pediatric cases, non-primary healthcare referrals over primary healthcare referrals, yellow triage over green, and female patients over males. Arrival patterns for day and night shifts were similar, except the child–adolescent category was not prioritized. Departure policy was influenced by payment method and discharge status in all shifts. The findings highlight the need for shift-based arrival and discharge policies to optimize EDLOS management in emergency care.Keyword: length of stay, hospital, emergency visit, emergency department AbstrakLama dirawat di unit gawat darurat (EDLOS) merupakan indikator utama kualitas layanan rumah sakit. Waktu tunggu yang panjang di IGD dapat menyebabkan penumpukan pasien, peningkatan risiko kejadian tidak diinginkan, keterlambatan penanganan, perpanjangan hari rawat inap, serta tingginya angka kematian. Penelitian ini bertujuan untuk mengevaluasi kebijakan kedatangan dan kepulangan pasien guna mengendalikan EDLOS di sebuah rumah sakit pemerintah daerah kelas B di Jakarta Barat. Penelitian ini menggunakan pendekatan kuantitatif dengan menganalisis 30.710 data kunjungan IGD dan 18.036 data triase dari Januari hingga Desember 2022. Pengambilan sampel dilakukan secara total sampling. Analisis regresi logistik biner bivariate digunakan untuk mengevaluasi kebijakan kedatangan, sementara model linier general digunakan untuk kebijakan kepulangan. Hasil menunjukkan bahwa median EDLOS adalah 4 jam 32 menit, dengan 22,7% kasus melebihi standar pelayanan 8 jam. Kebijakan kedatangan pada shift pagi berbeda dengan shift siang dan malam, sedangkan kebijakan kepulangan relatif sama di semua shift. Untuk mencegah EDLOS > 8 jam pada shift pagi, prioritas diberikan kepada pasien anak-remaja, dewasa, dan lansia dibanding balita, kasus psikiatri dibanding kasus anak, rujukan non-puskesmas dibanding dari puskesmas, serta triase kuning dibanding hijau. Pasien perempuan juga diprioritaskan dibanding laki-laki. Kebijakan kedatangan pada shift siang dan malam serupa, namun tanpa prioritas pada kelompok anak-remaja. Kebijakan kepulangan dipengaruhi oleh metode pembayaran dan status akhir pasien. Hasil ini menunjukkan pentingnya perbedaan kebijakan kedatangan dan kepulangan berdasarkan shift untuk mengoptimalkan pengelolaan EDLOS di layanan gawat darurat.Kata Kunci: lama rawat inap, rumah sakit, layanan gawat darurat, unit gawat darurat